Conductivity studies of chitosan based solid polymer electrolyte incorporated with ionic liquid - Kadir, M.F.Z.; Aspanut, Z.; Majid, S.R.; Arof, Abdul Kariem (2009)
Chitosan.Nl-lal + I-butyl-3-methylimidazolium iodide [BMIM][I] ionic liquid (IL) based polymer electrolyte were prepared by solution cast technique. The ratio of chitosan and ammonium iodide (NI-4I) salts was fixed at 55:45 (wt. %). Various concentrations of ionic liquid incorporated into the chitosan.Nllal films have been studied. The highest room temperature ionic conductivity was obtained for the sample containing 80 wt. % IL with the value of 8.47 x 10-4S cm-I. Dielectric properties of this film have been studied in the temperature range 303 K to 343 K. The AC conductivity was found to increase with increasing frequency and temperature. The plot of AC conductivity versus frequency follows the Jonscher power law <JAC = Aros